Involvement of endoplasmic reticulum stress in trigeminal ganglion corneal neuron injury in dry eye disease - Zhang, Jinyu; Lin, Hongbin; Li, Fengxian; Wu, Kaili; Yang, Shuangjian; Zhou, Shiyou (Frontiers in Molecular Neuroscience, 2023)
Dry eye disease (DED) is a multifactorial disease with a high prevalence worldwide. Uncomfortable corneal sensations severely affect daily life in DED patients. Hence, corneal neuron injury is a vital pathogenesis in DED. Notably, endoplasmic reticulum stress (ERS) plays a role in peripheral neuron injury. However, the role of ERS in DED corneal neuron injury is still far from being clear. In this study, we established an environmental DED (eDED) model in vivo and a hyperosmotic DED model in vitro. Subsequently, trigeminal ganglion (TG) corneal neurons were retrograde labeled by WGA-Alexa Fluor 555, and fluorescence-activated cell sorting was used to collect targeted corneal neurons for RNA sequencing in mice. Our results revealed that there is TG corneal neuron injury but not neuron apoptosis in DED. ERS-related genes and proteins were upregulated in TG corneal neurons of the eDED mice. ERS inhibition alleviated TG corneal neuron’s ERS-related injury. Therefore, ERS-induced TG corneal neuron injury may be an important pathomechanism and provide a promising therapeutic approach to DED.